In vivo measurement of PDE10A enzyme occupancy by positron emission tomography (PET) following single oral dose administration of PF-02545920 in healthy male subjects. (1st May 2017) - Delnomdedieu, Marielle; Forsberg, Anton; Ogden, Adam; Fazio, Patrik; Yu, Ching-Ray; Stenkrona, Per; Duvvuri, Sridhar; David, William; Al-Tawil, Nabil; Vitolo, Ottavio V.; Amini, Nahid; Nag, Sangram; et al.
Abstract: Phosphodiesterase 10A (PDE10A) is an enzyme highly enriched in the striatal medium spiny neurons. It is involved in the regulation of cytoplasmic levels of cAMP and cGMP and signaling within the basal ganglia. This study with PDE10A radioligand [ 18 F]MNI-659 was designed to measure the enzyme occupancy of PF-02545920 in 8 healthy male volunteers (48 ± 4 years) after a single oral dose (10 mg or 20 mg) and to evaluate safety and tolerability. Arterial blood sampling was performed to obtain a metabolite-corrected plasma input function for the quantification of [ 18 F]MNI-659 binding to PDE10A. The occupancy of PF-02545920 was calculated with two different methods: In Method 1, [ 18 F]MNI-659 enzyme occupancy was calculated from the estimates of binding potential, using the cerebellum as a reference region; in Method 2, occupancy was estimated from the slope of the revised Lassen's plot. Serum concentrations of PF-02545920 were measured to determine the relationship between concentration and occupancy. Based on Method 1, striatal PDE10A occupancy increased with increasing PF-02545920 dose: 14–27% at 10 mg dose (N = 4) and 45–63% at 20 mg dose (N = 3). Comparable occupancies were observed using Lassen's plot Method 2: 10 mg: 14–37%; 20 mg: 46–55%. The relationship between exposure and occupancy was best described using an Emax model. The serum concentration associated with 50% occupancy was estimated to be 93.2 ng/mL. Single oral doses of 10 mg or 20 mg of PF-02545920 were safe and well tolerated in healthy male volunteers [NCT# 01918202]. Highlights: Single oral doses (10 mg, 20 mg) of PF-02545920 were safe and well tolerated in healthy male volunteers. Enzyme occupancy of PF-02545920 obtained using [ 18 F]MNI-659 PET was in the expected range. Striatal PDE10A occupancy increased with increasing PF-02545920 dose and exposure, reaching ∼50% following the 20 mg single dose. A 20 mg oral dose of PF-02545920 provides sufficient target brain occupancy for evaluation in future PDE10 clinical trials.